3. Peningkatan Hasil Belajar Matematika Tema 3 Sub Tema 2 Melalui Model Kooperatif Tipe Think Phaire Share (Tps) Pada Siswa Kelas III SDN UJUNG XIII/38 Surabaya Tahun Pelajaran 2015/2016 - Ichtifaroh, Illa; Hidayati, Fitria (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
On the basis of the problems found in SDN End XIII / 38 Surabaya note that teachers who have not been using innovative teaching, teachers are still teaching with lectures and monotonous so less foster interest and motivation in learning activities that lead students to become bored and become inactive in classroom learning activities that lead to student learning outcomes to be low. Therefore, the researchers used a model of cooperative mode Phare Think Share (TPS). Objectives to be achieved in this study as follows: to determine the learning outcome using cooperative learning model TPS data processing material form of tables and graphs in the third grade students of SDN End XIII / 38 Surabaya, pelajarn year 2015/2016. Sample III class researchers totaling 30 students with 12 female students and 18 male students.